Weight Loss As a Sociocultural Practice of Creating a Demanded Body in the Students’ Community - Russkikh, Ludmila; Grun, Elena (KnE Social Sciences, 2021)
This article discusses the sociocultural practice of weight loss as a mean of a demanded body design in the student’s community. The study was conducted in 2019 at the South-Ural State University (National Research University) in Chelyabinsk, in Russia. The research methodology uses quantitative approach. 350 students were questioned. The objectives of the research were to study students’ perceptions of the body in demand and methods of weight loss for the construction of the body in demand. The study was based on sociological theories: such as body theory, theory of social / sociocultural practice and the social constructivism theory. The survey has revealed a strong dependence of students’ desire to lose weight on the common opinion. 79% of those who have been told about his / her stoutness want to lose weight, and only 24% of those who have not been told about his / her stoutness has the desire to lose weight. A strong relationship was also found between the students’ attempt and the desire to lose weight, depending on the presence of excess pounds. The authors draw conclusions about the students’ gender difference in ideas about the demanded female and male body. For girls, the harmony of the female body is more important than such a characteristic for men (despite the fact that this is their only requirement), as well as the relief, which for the boys in the perception of the female body was not important. But the requirements for the lack of undesirable body characteristics are the same. The study has shown that the majority of respondents (72.0%) do not consider model parameters of the figure to be the standard. However, girls still relate to such ideals somewhat more favorably than boys. Perhaps this is due to the greater exposure of girls to the influence of the media, public opinion and advertising. The dependence of the attempt and desire to lose weight on the adoption of model parameters for the standard was not found. The study has determined that for the majority of students the sociocultural practice of weight loss is an important means of constructing their physicality. However, for only one third of the respondents, it turned out to be effective. At the same time, students are not ready for more radical measures to change their physicality. Keywords: demanded body, students’ community, sociocultural practice of losing weight, a demanded body design